Nomenclatural notes on some names in the Hieracium tenuiflorum group (Asteraceae) of the Alps - Fainelli, Federico; Gottschlich, Günter; Orsenigo, Simone (Phytotaxa, 2024)
The names belonging to the Hieracium tenuiflorum group (sect. Hieracium) as published by Zahn and others are discussed and typified. The accepted names are H. tenuiflorum, H. tenuiflorum subsp. austrosilvularum, H. tenuiflorum subsp. glaucoviolascens, H. tenuiflorum subsp. pictoprasinum, H. tenuiflorum subsp. pseudomerianum, H. tenuiflorum subsp. sebini and H. murorum subsp. nemorensifolium. Where possible, also names at the ranks lower than species and subspecies (i.e. varieties, subvarieties, forms and subforms) were typified. Hieracium tenuiflorum is typified by specimens preserved in Herbarium Bicknell. All the subspecies were typified by specimens preserved in G, PAV and TR, except H. tenuiflorum subsp. austrosilvularum whose original material went very likely lost. Eight varieties, two subvarieties, fifteen forms and three subforms were typified by specimens preserved in B, BASBG, G, GRM, PAV, TR and Z/ZT.